Developing Information System Prototype for Thesis Guidance using Waterfall Model - Meliala, Avando; Sulistyawati, Arum Kurnia; Soejono, Ajie Wibowo; Winardi, Sugeng; Kristian, Tadem Vergi (International Journal of Informatics and Computation, 2026)
This paper presents the design and implementation of a web-based thesis supervision management system developed using the Waterfall model as the primary software development framework. The Waterfall model was adopted due to its sequential and systematic structure, which ensured that each development phase. We employed a process-oriented design methodology utilizing Context Diagrams and Data Flow Diagrams (DFDs) to model the interactions among three primary external actors, namely Academic Staff, Lecturers, and Students. An Entity-Relationship Diagram (ERD) was further constructed to establish a logically organized database structure aligned with the identified system requirements. We implemented the proposed system using PHP and MySQL within an XAMPP server environment, incorporating several core functional modules including user authentication, lecturer data management, thesis configuration, student dashboard, manuscript upload guidance, and supervision reporting. The disciplined phase-by-phase structure of the Waterfall model contributed significantly to the clarity, consistency, and completeness of the overall development process. Our proposed system clearly delineates actor roles and integrates all stakeholder interactions within a centralized digital platform, enabling real-time monitoring of thesis progress. The results confirm that our proposed system significantly improves transparency, reduces manual administrative workload, and enhances the efficiency and accuracy of thesis supervision management. This study affirms that the proposed method constitutes a viable and scalable solution for academic institutions seeking to modernize and streamline their thesis supervision processes.